(untitled) (Journal of Economic Research & Business Administration, 2015)
In this article learned the basis concepts of financial tools, which necessity in definition their contents and directions. Definite the principles belong in to the basis directions of the concepts of financial tools and specified their contents in accordance with IFRS.